Sustainability assessment from development indicators of community and sustainable development guidelines for the Huay Pao highland development project using royal project system - Taitaemthong, B.; Intaruccomporn, W.; Chalermphol, J.; Na Lampang, D.; Prapatigul, P. (International Journal of Agricultural Technology, 2019)
The community sustainability was investigated by developing sustainability indicators and Sustainable Development Guidelines for the Huay Pao Highland Development Project Using Royal Project System, Thungkhaopuang sub-district, Chiang Dao district, Chiangmai province. The selection of areas by experts of Highland Research and Development Institute (Public Organization). The population of this study was 50 persons. Data were recorded between October to December 2017 by focus group discussion and the structure interview. The focus group discussion could synthesis of sustainability indicators with community. It can be divided into 4 factors, total 32 indicators including 10 indicators of economic factor, 8 indicators of social factor, 7 indicators of environment factor and 7 indicators of infrastructure factor. The results of the community sustainability assessment from the developing sustainable indicators found that a community of the Huay Pao highland development project using Royal Project system had a strong focus on 4 factors. The overall sustainability assessment of the community was a very good level. Except for the environment factor was a good sustainable of the community. However, this community of the Huay Pao highland development project using Royal Project system is accelerated by the development of the economy factor for saving, knowledge in career development, and food security. Social factor was the strengthed development of leaders and peoples in the community, and promoted the establishment of farmers' institutions. Environment factor was promoted the soil and water conservation, increasing forest area, the community forest, and protection the external threats. Infrastructure factor was development of electricity services in the area, improve the services of the District Health Promotion Hospital, and developed the remote communities that provided to access both formal and informal systems. It is suggested to develop community should concern the needs of the community into consideration. Also, in the development of the highland community, it is important to focus on working in integrated with relevant agencies.